Médecine et sexualité, aperçus sur une rencontre historiographique (Recherches francophones, époques moderne et contemporaine) - Chaperon, Sylvie; Hanafi, Nahema (Clio. Femmes, Genre, Histoire, 2013)
Cet article rappelle dans quelles circonstances une histoire de la sexualité construite à partir de sources médicales a émergé en France dans les années 1970. Il insiste surtout sur les pionnier-e-s de cette histoire pour les périodes moderne et contemporaine et les sources qu’ils et elles ont utilisées. Enfin il met en avant le renouvellement récent de ce champ grâce à une histoire « par en bas ».
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; corps; cours; discipline; discours dominant; europe; france; histoire et politique; justice sociale; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; violences

Indigenous youth participatory action research: Re-visioning social justice for social work with indigenous youths - Johnston-Goodstar, Katie (Social Work, 2013)
The NASW Code of Ethics identifies social justice as one of six foundational values of the social work profession. Indigenous communities have long questioned the authenticity of this commitment and rightly so, given the historical activities of social work and social workers. Still, the commitment persists as an inspiration for an imperfect, yet determined, profession. This article presents a theoretical discussion of questions pertinent for social justice in social work practice in Native American communities: Whose definition of social justice should prevail in work with and in Indigenous communities? What can a revisioning of social justice mean to the development of Native communities and for Native youths in particular? What methods or processes of social work are most appropriate for this social justice work? This article presents a case for the practice of youth participatory action research as one method to work for social justice in Native communitie
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; autochtones; discipline; jeunes; justice sociale; périodes historiques; régions géographiques; sciences humaines; thématiques; travail; travail social; états-unis

Feminist, queer, crip - Kafer, Alison (Indiana University Press, 2013)
Select all Front Matter (pp. i-vi) Front Matter (pp. i-vi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.1 Table of Contents (pp. vii-viii) Table of Contents (pp. vii-viii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.2 Acknowledgments (pp. ix-xii) Acknowledgments (pp. ix-xii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.3 Textual Description of the Cover Art (pp. xiii-xvi) Textual Description of the Cover Art (pp. xiii-xvi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.4 Introduction: Imagined Futures (pp. 1-24) Introduction: Imagined Futures (pp. 1-24) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.5 I have never consulted a seer or psychic; I have never asked a fortune-teller for her crystal ball. No one has searched my tea leaves for answers or my stars for omens, and my palms remain unread. But people have been telling my future for years. Of fortune cookies and tarot cards they have no need: my wheelchair, burn scars, and gnarled hands apparently tell them all they need to know. My future is written on my body. In 1995, six months after the fire, my doctor suggested that my thoughts of graduate school were premature, if not misguided. He... 1 Time for Disability Studies and a Future for Crips (pp. 25-46) 1 Time for Disability Studies and a Future for Crips (pp. 25-46) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.6 What would it mean to explore disability in time or to articulate “crip time”? Temporal categories are already commonly used in formulations of disability; one aspect of cripping time might simply be to map the extent to which we conceptualize disability in temporal terms. The medical field in particular has a long tradition of describing disability in reference to time. “Chronic” fatigue, “intermittent” symptoms, and “constant” pain are each ways of defining illness and disability in and through time; they describe disability in terms of duration. “Frequency,” “incidence,” “occurrence,” “relapse,” “remission”: these, too, are the time frames of symptoms, illness,... 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.7 In thinking about crip futurity, I find myself haunted by Ashley X. Born in 1997, the girl known as Ashley X was diagnosed with “static encephalopathy” a few months after her birth. “In the ensuing years,” doctors note, “her development never progressed beyond that of an infant,” and her doctors held no hope that her cognitive or neurological baseline would improve.¹ “At the age of 6 years, she [could] not sit up, ambulate, or use language.”² Concerned about their daughter’s long-term future, Ashley’s parents met with doctors in 2004 to discuss the potential effects of puberty and physical growth on... 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.8 The pervasiveness of prenatal testing, and especially its acceptance as part of the standard of care for pregnant women, casts women as responsible for their future children’s able-bodiedness/able-mindedness; prospective parents are urged to take advantage of these services so as to avoid burdening their future children with any disabilities.¹ This notion of “burdening” children finds an echo in the debate over same-sex marriage, with LGBT couples cast as selfish parents, placing their own desires over the physical and mental health of their children (and, by extension, of all children). Moreover, according to Timothy Dailey of the Family Research Council, homosexual... 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.9 “Super man,” the billboard exclaims, the unfamiliar gap between the two words emphasizing both the noun and its adjective. Below this phrase is the word “STRENGTH,” followed by the imperative “Pass It On.” At the bottom, in small print, runs the name and web address of the organization behind this public relations campaign: Values.com/Foundation for a Better Life. The “super man” referenced in the caption is, of course, the late Christopher Reeve, the white actor who starred in a series ofSupermanfilms in the 1980s before becoming a quadriplegic in a riding accident in 1995. A black-and-white photograph of... 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.10 Controversy came quickly to the cyborg. In 1983,Socialist Reviewinvited several feminist theorists, among them Donna Haraway, “to write about the future of socialist feminism in the context of the early Reagan era.”¹ Haraway responded with “A Manifesto for Cyborgs,” framing the cyborg as a figure of feminist critique.² Her cyborg was a radical border-crosser, blurring the boundaries between human and animal, machine and organism, physical and non-physical.³ Such a cyborg, she argued, could “guide us to a more livable place,” an “elsewhere,” in which “people are not afraid of their joint kinship with animals and machines, not afraid... 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.11 Although concern with the environment has long been an animating force in disability studies and activism, “environment” in this context typically refers to the built environment of buildings, sidewalks, and transportation technologies. Indeed, the social model of disability is premised on concern for the built environment, stressing that people are disabled not by their bodies but by their inaccessible environments. (The wheelchair user confronting a flight of steps is probably the most common illustration of this argument.) Yet the very pervasiveness of the social model has prevented disability studies from engaging with the wider environment of wilderness, parks, and nonhuman... 7 Accessible Futures, Future Coalitions (pp. 149-170) 7 Accessible Futures, Future Coalitions (pp. 149-170) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.12 When describing disability studies to my students, I often draw on Douglas Baynton’s insight that “disability is everywhere in history once you begin looking for it.”¹ For Baynton, “looking for it” entails not only recovering the stories of disabled people or tracing histories of disability discrimination but also exploring how notions of disability and able-mindedness/able-bodiedness have functioned in different contexts. Baynton issues his provocation to historians, but disability studies scholars in other fields have extended its reach, pushing their own colleagues to recognize disability as a category of analysis. Deeply influenced by and indebted to this work, I use this... Appendices (pp. 171-178) Appendices (pp. 171-178) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.13 Notes (pp. 179-224) Notes (pp. 179-224) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.14 Bibliography (pp. 225-252) Bibliography (pp. 225-252) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.15 Index (pp. 253-258) Index (pp. 253-258) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.16 Back Matter (pp. 259-259) Back Matter (pp. 259-259) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.17 Indiana University Press logo Front Matter Download XML Table of Contents Download XML Acknowledgments Download XML Textual Description of the Cover Art Download XML Introduction:: Imagined Futures Download XML Time for Disability Studies and a Future for Crips Download XML At the Same Time, Out of Time:: Ashley X Download XML Debating Feminist Futures:: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians Download XML A Future for Whom?: Passing on Billboard Liberation Download XML The Cyborg and the Crip:: Critical Encounters Download XML Bodies of Nature:: The Environmental Politics of Disability Download XML Accessible Futures, Future Coalitions Download XML Appendices Download XML Notes Download XML Bibliography Download XML Index Download XML Back Matter Download XML ABOUT US About JSTOR Mission and History JSTOR Labs JSTOR Daily News Webinars Careers EXPLORE CONTENT What's in JSTOR Advanced Search By Subject By Title Collections Publisher Images RESEARCH TOOLS Data for Research The JSTOR Understanding Series Constellate HELP CENTER Get Support Get Access LibGuides Research Basics Contact Us For Librarians For Publishers Teaching Resources JSTOR is part of ITHAKA, a not-for-profit organization helping the academic community use digital technologies to preserve the scholarly record and to advance research and teaching in sustainable ways.©2000‍–2024 ITHAKA. All Rights Reserved. JSTOR®, the JSTOR logo, JPASS®, Artstor®, Reveal Digital™ and ITHAKA® are registered trademarks of ITHAKA. Terms & Conditions of Use Privacy Policy Accessibility Cookie Policy Cookie Settings Description In Feminist, Queer, Crip Alison Kafer imagines a different future for disability and disabled bodies. Challenging the ways in which ideas about the future and time have been deployed in the service of compulsory able-bodiedness and able-mindedness, Kafer rejects the idea of disability as a pre-determined limit. She juxtaposes theories, movements, and identities such as environmental justice, reproductive justice, cyborg theory, transgender politics, and disability that are typically discussed in isolation and envisions new possibilities for crip futures and feminist/queer/crip alliances. This bold book goes against the grain of normalization and promotes a political framework for a more just world.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; care; corps; cours; crip; discipline; future; identités LGBTQIA2+; intersectionnalité; justice sociale; philosophie; premier cycle; périodes historiques; queer; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1920; thématiques; études critiques du handicap

Le mariage forcé au Canada: la criminalisation, une solution ? - Lamboley, Madeline; Jimenez, Estibaliz; Cousineau, Marie-Marthe; Wemmers, Jo-Anne (Criminologie, 2013)
Cet article met en exergue les nombreuses difficultés éprouvées par les femmes victimes de mariage forcé. Celles-ci sont doublement vulnérables du fait, d’une part, des formes d’abus et d’exploitation dont elles peuvent être l’objet et, d’autre part, de leur statut parfois précaire d’immigrantes, en particulier lorsqu’elles sont parrainées par leur conjoint. Des études menées dans certains pays européens, notamment en Norvège et en Belgique, ont mis au jour une situation inattendue, vu l’ampleur que prenait la problématique, signalant une certaine urgence d’agir. Ces pays ont alors fait le choix de criminaliser la pratique des mariages forcés. Le Canada n’a pas pris une telle initiative. À partir d’une étude menée à la fois auprès de femmes vivant, ayant vécu ou étant menacées d’une situation de mariage forcé et d’informateurs clés provenant de divers milieux de pratique oeuvrant auprès d’elles, nous posons la question : la criminalisation est-elle la bonne, voire la seule, solution au problème envisagé ?
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; canada; cours; criminologie; discipline; inégalités; justice sociale; mariage; mariage forcé; montréal; patriarcat; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; violences

25 ans plus tard… et toujours nécessaires! Les approches structurelles dans le champ de l’intervention sociale - Lapierre, Simon; Levesque, Joscelyne (Reflets, 2013)
De manière générale, les approches structurelles reposent sur les deux principes suivants : 1. reconnaître que les situations individuelles sont intimement reliées aux structures politiques, sociales et économiques; 2. reconnaître que la réalisation de changements significatifs dans les situations auxquelles les individus sont confrontés exige aussi des changements dans les structures politiques, sociales et économiques et que de tels changements sont possibles. Ainsi, les approches structurelles sont considérées comme étant des approches critiques, conflictuelles et radicales, tout comme les approches antiracistes et antioppressives, ainsi que certaines approches féministes. Elles s’appuient sur des valeurs de justice sociale, d’égalité et de solidarité. Le présent article s’intéresse aux dimensions théoriques et pratiques, mais se penche d’abord sur les défis auxquels sont confrontées les intervenantes qui souscrivent aux approches structurelles dans l’intervention sociale contemporaine. La deuxième partie de l’article présente les principaux éléments d’analyse sur lesquels s’appuient les approches structurelles, ainsi que leur pertinence dans le contexte actuel. La troisième partie de l’article se penche davantage sur l’application de ces approches en fonction de trois cibles d’intervention (individuelle, groupe et collective) ainsi que sur les habiletés d’intervention nécessaires
Keywords: approche structurelle; approches et analyses; cours; discipline; droit; droits des femmes*; justice sociale; science politique et droit; sciences humaines; thématiques; travail social; trs3500

Femmes et handicap - Masson, Dominique (Recherches féministes, 2013)
Les femmes handicapées, leurs réalités et leurs combats sont encore largement absents du courant de pensée majoritaire (mainstream) en études féministes qui, malgré un virage récent vers les analyses intersectionnelles, demeurent peu au fait des modalités d'analyse du handicap et des oppressions fondées sur les (in)capacités. Cet article veut permettre à un lectorat francophone de se familiariser avec les principales bases conceptuelles utilisées pour théoriser le handicap et les (in)capacités développées dans le domaine des études critiques du handicap, et en particulier par les auteures féministes travaillant dans ce champ. Il vise également à contribuer aux connaissances féministes des enjeux de transformation sociopolitique qui sont centraux pour les femmes handicapées, tels que ceux-ci sont révélés par les luttes de l'organisation féministe Action des femmes handicapées (Montréal). En conclusion, l'auteure explique la raison pour laquelle le handicap doit être considéré comme un enjeu féministe
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; canada; capacitisme; care; corps; cours; discipline; histoire et politique; intersectionnalité; justice sociale; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études féministes

Porno? Chic!: how pornography changed the world and made it a better place - McNair, Brian (Routledge, 2013)
Porno? Chic! examines the relationship between the proliferation of pornography and sexualised culture in the West and social and cultural trends which have advanced the rights of women and homosexuals. Brian McNair addresses this relationship with an analysis of trends in sexualised culture since 2002 linked to a transnational analysis of change in sexual politics and sex/gender relations in a range of societies, from the sexually liberalised societies of advanced capitalism to those in which women and homosexuals remain tightly controlled by authoritarian, patriarchal regimes. In this accessible, jargon-free book, Brian McNair examines why those societies in which sexualised culture is the most liberalised and pervasive are also those in which the socio-economic and political rights of women and homosexuals have advanced the most.
Keywords: LGBTQIA2+; approches et analyses; communication; cours; discipline; droits des femmes*; féminisme pop; identités LGBTQIA2+; justice sociale; premier cycle; queer; sciences humaines; sciences sociales; sex1911; sexualité; thématiques; études culturelles

Le travail social entre émancipation et normalisation : une voie étroite pour les approches féministes - Modak, Marianne; Martin, Hélène; Keller, Véréna (Nouvelles Questions Feministes, 2013)
Édito
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem7000; féminisme matérialiste; histoire et politique; justice sociale; point de vue situé; pratiques féministes; rapports sociaux de sexe; sciences humaines; thématiques; théorie critique; travail social; émancipation

Genre, migrations et globalisation de la reproduction sociale - Verschuur, Christine; (Dir), Christine Catarino; Par, Dirigé. (L'Harmattan, 2013)
Les études féministes ont souligné l’importance d’étudier le travail auparavant invisible des femmes, productif et reproductif, et la nouvelle division du travail productif et reproductif dans la mondialisation du capitalisme. L’analyse du capitalisme mondialisé dans une perspective décoloniale permet de comprendre qu’il n’est pas seulement un système économique ni seulement un système culturel mais un réseau global de pouvoir intégré par des processus économiques, politiques et culturels qui constituent un ensemble. Partout on observe un système, social, économique, culturel, moral d’organisation de la reproduction sociale, y compris le care, entendu comme échange économico-affectif, qui implique des biens et des services liés à l’économie capitaliste. Dans le nouvel ordre économique global, que l’on pourrait toujours qualifier de colonial, caractérisé par la nouvelle division internationale du travail, l’articulation entre rapports sociaux dans l’économie domestique et capitaliste prend de nouvelles formes. Mais le système repose toujours sur l’organisation de l’ensemble des activités et des rapports indispensables à la reproduction sociale, par-delà les frontières, dans des réseaux et foyers transnationaux, en s’appuyant sur des discours de genre et de race, voire de classe. Dans ce système, les femmes migrantes sont particulièrement présentes. Elles constituent un maillon essentiel du système de protection sociale aux Nords, y contribuent à la production de richesses, tout en assurant l’organisation de la reproduction sociale aux Suds, dans les foyers qu’elles ont gardés dans leurs pays d’origine.
Keywords: approches et analyses; capitalisme; care; cours; discipline; féminisme décolonial; globalisation; intersectionnalité; justice sociale; militance; pol4022; premier cycle; ressource en ligne; science politique; science politique et droit; sciences humaines; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; travail; travail du sexe